2021
DOI: 10.1080/02656736.2021.1933616
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of thermal washout due to spatiotemporally heterogenous perfusion in the application of a model-based control algorithm for MR-HIFU mediated hyperthermia

Abstract: Purpose: This article will report results from the in-vivo application of a previously published model-predictive control algorithm for MR-HIFU hyperthermia. The purpose of the investigation was to test the controller's in-vivo performance and behavior in the presence of heterogeneous perfusion. Materials and methods: Hyperthermia at 42 C was induced and maintained for up to 30 min in a circular section of a thermometry slice in the biceps femoris of German landrace pigs (n¼5) using a commercial MR-HIFU system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…A novel approach based on induction of hyperthermia by scanning a high intensity focused ultrasound beam through the tumor volume is under development, but its use in humans needs to be tested. 51 Reliable hyperthermia delivery also requires real time temperature monitoring using minimally invasive temperature probes Review inserted in the vagina/cervix, bladder, and rectum. Non-invasive MRI based thermometry is under development, but its accuracy is presently still strongly limited by motion artifacts, and about half of the patients do not fit into the small bore of the hybrid MRI guided locoregional hyperthermia device.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel approach based on induction of hyperthermia by scanning a high intensity focused ultrasound beam through the tumor volume is under development, but its use in humans needs to be tested. 51 Reliable hyperthermia delivery also requires real time temperature monitoring using minimally invasive temperature probes Review inserted in the vagina/cervix, bladder, and rectum. Non-invasive MRI based thermometry is under development, but its accuracy is presently still strongly limited by motion artifacts, and about half of the patients do not fit into the small bore of the hybrid MRI guided locoregional hyperthermia device.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Radiative locoregional hyperthermia devices are currently optimal for achieving therapeutic temperatures in deep seated tumors, such as in cervical cancer. A novel approach based on induction of hyperthermia by scanning a high intensity focused ultrasound beam through the tumor volume is under development, but its use in humans needs to be tested 51. Reliable hyperthermia delivery also requires real time temperature monitoring using minimally invasive temperature probes inserted in the vagina/cervix, bladder, and rectum.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…They used the bio‐heat transfer equation (BHTE) model and temperature information acquired with invasive probes 25 . For high‐intensity focused ultrasound (HIFU), several studies employed filtering in combination with MR thermometry to improve the temperature estimation 26,27 . Roujol et al 28 .…”
Section: Introductionmentioning
confidence: 99%
“…25 For high-intensity focused ultrasound (HIFU), several studies employed filtering in combination with MR thermometry to improve the temperature estimation. 26,27 Roujol et al 28 employed a Kalman filter combined with MR thermometry and showed a threefold accuracy improvement for temperature estimation when heating a phantom and a porcine kidney. Zhang et al 29 and Schmitt et al 30 have shown combining Kalman filtering with MR thermometry to improve the temperature monitoring accuracy on patient data using HIFU.…”
Section: Introductionmentioning
confidence: 99%
“…These verification measurements are aimed at improving the translation of hyperthermia treatment planning (HTP) settings into the clinical routine. While quality assurance measurements make HTP a more reliable tool to ensure target conformal electromagnetic field energy delivery, the uncertainties in tissue electromagnetic and thermal properties affect the reliability of the model based predicted temperatures [ 19 , 20 , 21 ]. Hence, detailed temperature measurements, both in the target region and healthy tissues, are required to assess the true temperatures achieved and to enable dynamic adaptation of the power distribution for maximizing the applied thermal dose.…”
Section: Introductionmentioning
confidence: 99%